Measuring effective communication as a tool for achieving organizational objective in Pejabat Setiausaha Kerajaan Negeri Sembilan / Nuralifah Ilyana Hamdan - Hamdan, Nuralifah Ilyana (Faculty of Business and Management, 2018)
Communication is the process of changing the information between individual by using a symbols, signs or behaviour. It is referring to the process of information being transmitted and understood between two or more people. In business and industry, communication helps to align employees to work with each other and achieve the objective of the organization. Without workplace communication, nothing can be done. So, the purpose of this research is measuring the effective communication as a tool for achieving organizational objective in Pejabat Setiausaha Kerajaan Negeri Sembilan. This research determines which factors of effective communication that influence organizational objective. 127 respondents were involved in this study. By using multiple regression analysis, all variables are proven to have positive relationship with organizational objective. The three positively significant variables are communication climate, supervisor communication and subordinate communication. Based on the analysed results, the research discusses the implications of the results and suggest a few recommendations for future research.